Breastfeeding Support and Facilities for Mothers in the Workplace - Yundar Indrawanto; Bunga Astria Paramashanti; Hamam Hadi; Nur Indah Rahmawati; Faza Kilwan Amna (Alma Ata University Press, 2017)
Exclusive breastfeeding is the fulfillment of infants and mothers’ rights. However, the coverage of exclusive breastfeeding remained low. This study aimed to understand the breastfeeding support and facilities at the workplace in the implementation of exclusive breastfeeding among working mothers. This study was conducted in companies in the area of Bantul District. Design in this study was qualitative design with phenomenology approach. Participants were selected by using purposive sampling methods. Based on the interview, participants received breastfeeding support from employers but it was not supported by written policy on the management of exclusive breastfeeding at the workplace. This might affect on the availability of lactation room and the facilities provided in the lactation room, maternity leave which was considered inadequate, no break time for lactating or pumping the breastmilk, and neither childcare at the workplace or child care that was near to the workplace. In conclusion, breastfeeding support and facilities at the workplace would give benefits in the implementation of exclusive breastfeeding among working mothers.